2018
DOI: 10.1111/jdv.15327
|View full text |Cite
|
Sign up to set email alerts
|

HrQoL in hair loss‐affected patients with alopecia areata, androgenetic alopecia and telogen effluvium: the role of personality traits and psychosocial anxiety

Abstract: Background Illness impact on HrQoL has been widely studied in hair loss‐affected patients, yet no study has addressed whether individual differences modulate HrQoL in patients with alopecia areata (AA), androgenetic alopecia (AGA) and telogen effluvium (TE). Objective To identify the personality dimensions most predictive of the impact of disease on HrQoL. Method A single‐site cross‐sectional study was carried out in the Dermatology Unit of Sant'Orsola‐Malpighi Hospital, Bologna between September 2016 and Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 20 publications
(42 reference statements)
2
58
0
1
Order By: Relevance
“…For example, only in Turkey was more than one of the relevant studies conducted and published. In general, however, the results underscore the psychosocial burden that can be triggered by hair loss [4,9,33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, only in Turkey was more than one of the relevant studies conducted and published. In general, however, the results underscore the psychosocial burden that can be triggered by hair loss [4,9,33].…”
Section: Discussionmentioning
confidence: 99%
“…Hair loss will affect most men and women at some point during their lifetime, causing increased anxiety and decreased self‐esteem 1,2 . While there are many nonsurgical therapies available (eg, minoxidil, finasteride, thickening shampoos, and vitamins), the most effective can have adverse side effects, such as the case with finasteride and sexual dysfunction, and all must be used continuously for long‐term results.…”
Section: Introductionmentioning
confidence: 99%
“…By embracing a diverse study population including those with mild and undiagnosed hair loss, we found a lower impact on QoL compared with other studies. 1,2,4,6 The strong racial component with Indians and South Asians (e.g. Pakistani, Sri Lankans) having worse QoL compared with Chinese and Malays highlights the cultural variation, with certain races placing more importance in the fullness of hair.…”
Section: Supporting Informationmentioning
confidence: 99%